A comparative study of virtual and insite engineering service-learning implementations - Riaji, Tarek; El Hassani, Sanae; Seo, Young Bong; Alaoui, Fatima Ezzahrae M'hamdi (Journal of Education and Learning (EduLearn), 2024)
The Smile project is an engineering service-learning initiative carried out through collaboration between Chouaib Doukkali University in Morocco and Pusan National University in South Korea. Since 2016, this project has been conducted annually for engineering students from both universities. Participants are selected through an oral interview, ensuring representation from different majors, years, and genders. Due to the COVID-19 pandemic, the project transitioned to an online mode starting from 2020. The objective of this article is to investigate the impact of the service-learning approach on learning and its potential for enhancing engineering education. This study aims to compare the face-to-face and online implementations of the Smile project as examples of this educational approach. The analysis demonstrates a strong positive effect of engineering service-learning as a learning approach, leading to the improvement of engineering students' skills and competencies. Notably, there is minimal difference between the two implementation modes of this learning approach.